Fast twitch fibers may predict anaerobic performance in both females and males - Esbjornsson, M.; Sylven, C.; Holm, J.; Jansson, E. (International Journal of Sports Medicine, 1993)
Males and females with similar training backgrounds were analyzed for anaerobic performance and muscle characteristics. Whether there was any gender difference in the characteristics was also determined. Muscle biopsies and a 30 sec all out Wingate test on a bicycle ergometer were performed. Males were higher than females in peak power (44%), mean power (48%), total lactate dehydrogenase activity (33%), and substrate of LD (38%). Anaerobic performance was directly related to the proportion of type II fibers. Females differed only in muscle volume. Implication: Anaerobic performance is directly related to the quantity of fast-twitch fibers in muscles. The relationship is independent of gender while recognizing that females have less quantity of fibers. Adding further muscle qualities to a predictive equation does not increase the prediction of anaerobic performance.